2015
DOI: 10.1016/j.jconrel.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Bolaamphiphiles as carriers for siRNA delivery: From chemical syntheses to practical applications

Abstract: In this study we have investigated a new class of cationic lipids – “bolaamphiphiles” or “bolas” for their ability to efficiently deliver small interfering RNAs (siRNAs) to cancer cells. The bolas of this study consist of a hydrophobic chain with one or more positively charged head groups at each end. Recently, we reported that micelles of the bolas GLH-19 and GLH-20 (derived from vernonia oil) efficiently deliver siRNAs, while having relatively low toxicities in vitro and in vivo. Our previous studies validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
(50 reference statements)
2
27
0
Order By: Relevance
“…Nano‐TNAs have the potential to overcome both of these barriers. Their delivery to the brain can be achieved by previously characterized carriers, such as bolaamphiphiles, and rational design of nano‐TNAs can help avoid the undesirable neuroinflammation. Therefore, it is necessary to characterize the immunomodulatory effects of nano‐TNAs on resident CNS cells such as microglia and astrocytes that are essential for the initiation and progression of immune responses in the CNS through the production of various inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐TNAs have the potential to overcome both of these barriers. Their delivery to the brain can be achieved by previously characterized carriers, such as bolaamphiphiles, and rational design of nano‐TNAs can help avoid the undesirable neuroinflammation. Therefore, it is necessary to characterize the immunomodulatory effects of nano‐TNAs on resident CNS cells such as microglia and astrocytes that are essential for the initiation and progression of immune responses in the CNS through the production of various inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were observed in a more recent study in which two other bola micelle variants GLH-58 and GLH-60 were characterized both computationally and experimentally (in vitro). 243 GLH-58 and GLH-60 have hydrophobic cores derived from jojoba oil, and two (GLH-58) or four (GLH-60) GLH-20-like ACh head groups. 3D structure modeling and MD simulations (Figure 4), combined with experimental results indicated that the design differences between GLH-58 and GLH-60 influence the balance between the RNA protection against degradation, efficiency of delivery, and ease of RNA release.…”
Section: ■ Delivery Methods For Rna Therapeutics and Rna Npsmentioning
confidence: 99%
“…NANPs' molecular weight and structure are different from those of the traditional TNA. While NANPs versatility and strategies for design of functional NANPs have been studied extensively [46][47][48][49][50][51][52][53]55,57,[65][66][67][68][70][71][72][73][74][76][77][78][79][80][81]83,86,91,92,[95][96][97][98]100,102,103,121,[129][130][131][132][133][134][135][136][137][138][139][140][141]…”
Section: Translational Considerationsmentioning
confidence: 99%